Caracterização e análise de tendências a longo prazo de poluentes atmosféricos na região metropolitana de Curitiba, Brasil - Olivares, Lizeth Bibiana Castro (2020)
This work focuses on the characterization and spatiotemporal variability of the air quality in the Metropolitan Region of Curitiba (MRC) and its evolution over time. Several pollutants (SO2, NO2, NOx, O3, CO e PM10) measured at eight monitoring sites were studied in the period 20032017. The analysis was performed through statistical description of the concentrations, seasonal variability, diurnal cycles, identification of possible emission sources with the conditional bivariate probability function (CBPF), trend calculations with the nonparametric TheilSen estimator and comparison with the air quality national standards. In addition, trends were analyzed with respect to the implementation of programs or regulations to improve the air quality in the MRC. The sites that were strongly impacted by industrial emissions (CSN and RPR1) presented the highest mean annual concentrations of SO2 (2820 μg/m3) and PM10 (3234 μg/m3). However, the monitoring sites highly impacted by traffic emissions (PAR and UEG) showed high mean annual concentrations of NO2 (3139 μg/m3), NOx (6386 μg/m3) and CO (0.80.6 mg/m3). Mean annual O3 concentrations were highest (3032 μg/m3) at the two residential sites (BOQ and STC). Winter and summer showed the highest and lowest pollutant concentrations, respectively; however, O3 peaked in springtime. SO2 concentrations presented no clear seasonal or diurnal cycle patterns. The diurnal cycles of NO2, NOx and CO exhibited a similar pattern as the traffic volume, with peak values in the morning (8 am10 am) and evening (7 pm8 pm), mainly on weekdays. PM10 exhibited maximum concentrations at noon (11 am12 am) and night (10 pm11 pm). O3 reached its maximum in the afternoon (2 pm3 pm), associated with solar radiation and the chemical reactions of its precursors, and a secondary maximum in the early morning (2 am5 am), probably connected with the regional transport of O3 and/or its precursors. In addition, O3 concentrations were higher at weekends than on weekdays, due to the reduction in precursor concentrations. In the period 20032017, a statistically significant decrease in SO2, NO2, NOx, CO and PM10 concentrations was observed in most monitoring stations, with an annual reduction of 6.5, 4.0, 4.2, 7.7 and 5.5%, respectively. These results indicate that the emission reduction programs implemented over the years succeeded in improving the air quality in the MRC. However, O3 showed a significant increase (+5.8%/year) at some sites, mainly associated with a decrease in NOx concentrations, an increase in VOC emissions (due to the higher consumption of biofuels by the vehicle fleet), and the increase in regional transport of O3. The number of exceedances of the national air quality standards decreased over time. However, all pollutants, except for CO, still presented concentrations above the limit values recommended by the World Health Organization (WHO).